PARENTAL KNOWLEDGE AND PRACTICE TOWARDS FOREIGN BODY ASPIRATION IN CHILDREN - Jitlada Piriyasart,; Lee Siew Pien,; Nurul Hidayah Zukipli,; Norfadzilah Ahmad, (Journal of Islamic, Social, Economics and Development, 2024)
Foreign body aspiration is a frequently identified leading cause of mortality and respiratory crises in children aged 5 and below. This study aimed to assess parental awareness and behaviour concerning foreign body aspiration in children. Employing a random sampling method, a cross-sectional study was conducted among 160 parents in Pahang, Malaysia. Questionnaires were distributed via various social media platforms, and statistical analyses, including the Chi-square test for frequency comparison was applied. The findings revealed that 50% of participants exhibited proficient knowledge, while approximately 50.6% demonstrated inadequate practices regarding foreign body aspiration in young children. Additionally, a notable correlation was identified between gender and being a first-time parent in relation to knowledge and practices associated with foreign body aspiration in children. This study emphasizes the imperative role of healthcare institutions in organizing targeted educational workshops, specifically tailored for mothers and first-time parents, to elevate awareness and readiness for foreign body aspiration in children, thus effectively mitigating potential risks.